2020
DOI: 10.1002/acn3.51246
|View full text |Cite
|
Sign up to set email alerts
|

Motor beta cortical oscillations are related with the gait kinematics of youth with cerebral palsy

Abstract: Objective: It is widely believed that the perinatal brain injuries seen in youth with cerebral palsy (CP) impact neuronal processing of sensory information and the production of leg motor actions during gait. However, very limited efforts have been made to evaluate the connection between neural activity within sensorimotor networks and the altered spatiotemportal gait biomechanics seen in youth with CP. The objective of this investigation was to use magnetoencephalographic (MEG) brain imaging and biomechanical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 63 publications
(122 reference statements)
1
19
4
Order By: Relevance
“…These combined results indicate that the uncharacteristic motor actions seen in adults with CP may be partially attributable to the weaker sensorimotor beta oscillations. Interestingly, this nding differs from our prior studies in youth with CP, which have shown that the beta ERD is stronger in those with CP relative to their age-matched peers during lower extremity tasks [47][48][49] . This discrepancy may indicate that the neurophysiological mechanisms that govern cortical oscillatory activity during the respective motor tasks differ, such as differences in cognitive load and movement certainty, or it may be more re ective of developmental differences between youth and adults with CP.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…These combined results indicate that the uncharacteristic motor actions seen in adults with CP may be partially attributable to the weaker sensorimotor beta oscillations. Interestingly, this nding differs from our prior studies in youth with CP, which have shown that the beta ERD is stronger in those with CP relative to their age-matched peers during lower extremity tasks [47][48][49] . This discrepancy may indicate that the neurophysiological mechanisms that govern cortical oscillatory activity during the respective motor tasks differ, such as differences in cognitive load and movement certainty, or it may be more re ective of developmental differences between youth and adults with CP.…”
Section: Discussioncontrasting
confidence: 99%
“…Prior clinical investigations have shown that the strength of beta and gamma sensorimotor cortical oscillations are altered in youth with CP. Speci cally, several investigations have reported that the beta ERD within the primary motor cortex, the premotor cortex, and the supplementary motor area is stronger in youth with CP relative to age-matched controls during leg movements [47][48][49] . Furthermore, the gamma ERS has been shown to be weaker in youth with CP during a lower extremity motor task.…”
Section: Introductionmentioning
confidence: 99%
“…This specific association may be related by the existence of physiologically relevant occipitomotor, but not auditory-motor, functional connections [60]. Several previous MEG studies have supported the idea that greater motor impairments may be directly linked with altered integration between sensorimotor and visuo-perceptual modalities in youth with CP [2,61,62]. Together with the current work, these results further support the premise that the uncharacteristic gait seen in youth with CP may be driven by a disconnectivity between the sensorimotor and visual networks [63].…”
Section: Discussionmentioning
confidence: 91%
“…Cerebral palsy (CP) is the most prevalent pediatric neurologic impairment diagnosed in the United States and often results in lifelong mobility challenges [1]. The breadth of the muscular performance and sensory acuity deficiencies in youth with CP have largely fueled the impression that the altered spatiotemporal gait biomechanics primarily originate from aberrations in sensorimotor cortical activity [2][3][4][5]. Despite this impression, a growing body of literature has highlighted that youth with CP also have altered activity in the primary occipital cortices and visual MT areas while processing visual stimuli [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Some of them focused on differences in connectivity patterns between MI and ME [12] , [26] . The experimental method most frequently used to test the common-basis hypothesis for real vs. virtual movements is function magnetic resonance imaging (fMRI) [22] , [27] , Magnetoencephalography (MEG) [28] , near infrared spectroscopy (NIRS) [29] , and EEG. The primary motor cortex (M1) signals’ importance has been reported in providing the information necessary for BCI.…”
Section: Introductionmentioning
confidence: 99%